“Personal matters” of the officials in the Grodno province during the reign of Nicholas I based on archival materials of the National Historical Archives of Belarus in Grodno” - Kowalik, Jolanta (Marginesy, 2021)
As a consequence of the partitions and the annexation of the eastern lands of the Commonwealth, the citizens of the former Polish territory found themselves within the borders of the Russian Empire and became the subjects of the tsar. The government’s policy was aimed at transforming the annexed lands to the Russian manner, especially in the administrative aspect, and also consequently in the legislative one. The new reality forced people to change sovereignty and loyalty to a new monarch. Polish officials employed in the administration subordinate to the Russian authorities became a part of the same bureaucratic system as in Russia. The aim of the article is to present the social situation of officials from the Grodno province employed in the local administration during the reign of Tsar Nicholas I. I particularly focused on the officials from the lower positions. Analyzing the archival materials such as personal forms (formal conspiracies) or official correspondence found in the National Historical Archives of Belarus in Grodno, allowed me to stress the most important problems that representatives of this professional group were facing.